INTERNATIONAL ON THE ASSESSMENT OF THE QUALITY OF EDUCATION IN THE PUBLIC EDUCATION SYSTEM NORMATIVE FOR THE INTRODUCTION OF STUDIES (PISA, TIMSS, PIRLS) LEGAL GROUNDS (Neo Scientific Peer Reviewed Journal, 2023)
This article mentions measures and measures for the introduction of international studies on the assessment of the quality of education. Information is provided about the regulatory and legal basis of international assessment programs, their role in the educational system.